2008
DOI: 10.1007/s11746-008-1223-0
|View full text |Cite
|
Sign up to set email alerts
|

Laboratory Studies on Membrane Deoiling of Lecithin

Abstract: Deoiling of lecithin using a nonporous membrane was examined in a favorable solvent (hexane) medium with soy and rice bran lecithins. During the membrane process, the acetone insoluble (AI) content of soy lecithin increased from 63.2 to 81.0% in a single step batch operation. The membrane exhibited an excellent selectivity since phospholipid (PL) reverse micelles formed in the system were rejected almost completely due to low solubility probably aided synergistically by size exclusion. Diafiltration achieved g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…An ultrafiltrationbased process was developed in 1998 by Archer Daniels Midland Company (ADM, USA) using polyvinylidene fluoride membrane with a molecular weight cut-off (MWCO) of 10-50 kDa, which produced deoiled lecithin with a 90% AI content [10], a relatively high purity, although not reaching the deoiled lecithin standard set by the Central Soya Company [11]. A nonporous membrane based on the diafiltration process has also been used in deoiling lecithin [12], resulting in an increase in the AI content of soy lecithin from 63.2 to 81.0% in a single-step batch operation. Nonporous membranes were able to reject PL reverse micelles as well as their monomers.…”
Section: Introductionmentioning
confidence: 99%
“…An ultrafiltrationbased process was developed in 1998 by Archer Daniels Midland Company (ADM, USA) using polyvinylidene fluoride membrane with a molecular weight cut-off (MWCO) of 10-50 kDa, which produced deoiled lecithin with a 90% AI content [10], a relatively high purity, although not reaching the deoiled lecithin standard set by the Central Soya Company [11]. A nonporous membrane based on the diafiltration process has also been used in deoiling lecithin [12], resulting in an increase in the AI content of soy lecithin from 63.2 to 81.0% in a single-step batch operation. Nonporous membranes were able to reject PL reverse micelles as well as their monomers.…”
Section: Introductionmentioning
confidence: 99%
“…However, cost is a major concern as the processes are usually performed under high pressures and high temperatures. Manjula & Subramanian [2008] investigated the de-oiling of lecithin using a nonporous polymeric membrane and hexane as the solvent. Their results demonstrated that the membrane is a promising alternative for the de-oiling of lecithin, especially in terms of cost effectiveness.…”
Section: Modification Of Soy Lecithinmentioning
confidence: 99%